Chitotriosidase 1 in the cerebrospinal fluid as a putative biomarker for HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) progression - Gomes, Yago Côrtes Pinheiro; Freitas, Nicole Lardini; Souza, Flávia Santos; Sandim, Vanessa; Pereira, Denise Abreu; Nogueira, Fábio César Sousa; Echevarria-Lima, Juliana; Leite, Ana Claudia Celestino Bezerra; Lima, Marco Antonio Sales Dantas; Silva, Marcus Tulius Teixeira; Araújo, Abelardo Queiroz Campos; Vicente, Ana Carolina Paulo; et al. (Frontiers in Immunology, 2022)
Human T-lymphotropic virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is an inflammatory neurodegenerative disease that affects motor, urinary, intestinal, and sensory functions. Typically, HAM/TSP is slowly progressive, but it may vary from limited motor disability after decades (very slow progression) to loss of motor function in a few years from disease onset (rapid). In this study, we aimed to identify prognostic biomarkers for HAM/TSP to support patient management. Thus, proteomic analysis of the cerebrospinal fluid (CSF) was performed with samples from HTLV-1 asymptomatic carriers (AC) (n=13) and HAM/TSP patients (n=21) with rapid, typical, and very slow progression using quantitative label-free liquid chromatography/tandem mass spectrometry. Enrichment analyses were also carried out to identify key biological processes associated with distinct neurological conditions in HTLV-1 infection. Candidate biomarkers were validated by ELISA in paired CSF and serum samples, and samples from HTLV-1-seronegative individuals (n=9) were used as controls. CSF analysis identified 602 proteins. Leukocyte/cell activation, immune response processes and neurodegeneration pathways were enriched in rapid progressors. Conversely, HTLV-1 AC and HAM/TSP patients with typical and very slow progression had enriched processes for nervous system development. Differential expression analysis showed that soluble vascular cell adhesion molecule 1 (sVCAM-1), chitotriosidase 1 (CHIT1), and cathepsin C (CTSC) were upregulated in HAM/TSP. However, only CHIT1 was significantly elevated after validation, particularly in HAM/TSP rapid progressors. In contrast, none of these biomarkers were altered in serum. Additionally, CSF CHIT1 levels in HAM/TSP patients positively correlated with the speed of HAM/TSP progression, defined as points in the IPEC-2 HAM/TSP disability scale per year of disease, and with CSF levels of phosphorylated neurofilament heavy chain, neopterin, CXCL5, CXCL10, and CXCL11. In conclusion, higher CSF levels of CHIT1 were associated with HAM/TSP rapid progression and correlated with other biomarkers of neuroinflammation and neurodegeneration. Therefore, we propose CHIT1 as an additional or alternative CSF biomarker to identify HAM/TSP patients with a worse prognosis.